Custom measurement system for memristor characterisation. (December 2021) - Lupo, F.V.; Scirè, D.; Mosca, M.; Crupi, I.; Razzari, L.; Macaluso, R.
Highlights: Cheap and easily customisable memristors electrical characterisation system. Capability of performing retention, endurance and DC sweeps measurements. Capability of imposing a fine-tuneable current compliance. Abstract: A cheap, compact and customisable characterisation system for memristor devices, working between ± 10 V, is presented. SPICE (Simulation Program with Integrated Circuit Emphasis) simulations are performed to verify the circuit feasibility and a proper software is developed to drive the system. The potentiality of the realised system is tested by performing several electrical measurements on both Cu/HfO2 /Pt memristors and two-terminals commercial devices.